2020
DOI: 10.22271/tpi.2020.v9.i10e.5252
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence analysis in rice (Oryza sativa L.) under sodic soil condition

Abstract: Genetic divergence and variability was assessed among eighty eight (88) diverse rice genotypes including three checks (Narendra Usar Dhan 3, Jaya and CSR-36) which were evaluated in augmented deign under sodic soil using non-hierarchical Euclidean cluster analysis. The genotypes were grouped into ten clusters which indicate presence of high degree of genetic diversity in germplasm collections. Among the different clusters, cluster V with eighteen (18) entries got the highest number of genotypes followed by thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…In addition, this approach could be deployed to improve hybrid parental lines such as maintainer and restorer lines. This result conforms with previous studies for DFF [49:50], TPP [51][52][53][54], and TSP [36;53;55]. This study showed that high H 2 coupled with low GAPM were observed in GLT (H 2 = 79.78%, GAPM = 8.31%).…”
Section: Vp -Phenotypic Variance Vg Genotypic Variance Pcv -Phenotypi...supporting
confidence: 93%
“…In addition, this approach could be deployed to improve hybrid parental lines such as maintainer and restorer lines. This result conforms with previous studies for DFF [49:50], TPP [51][52][53][54], and TSP [36;53;55]. This study showed that high H 2 coupled with low GAPM were observed in GLT (H 2 = 79.78%, GAPM = 8.31%).…”
Section: Vp -Phenotypic Variance Vg Genotypic Variance Pcv -Phenotypi...supporting
confidence: 93%
“…Higher demonstration yield in this variety is attributed to its genetic potential and congenial environmental condition. Similar result had been obtained by Singh et al, (2022) & Raju et al, (2015) also recorded yield increment under cluster front line demonstration of pigeon pea. Singh et al, (2020a) also reported overall higher demonstrations yield of pigeon pea (1.28 to 1.73 t/ha) than the local practices in different varieties/ location.…”
Section: Demonstration Yield Of Varietiessupporting
confidence: 88%
“…The determination of the total lipid content in 10 g samples was performed with petroleum ether by Soxhlet based on the method described in ISO 659:2009 standard (ISO, 2009b). Total carbohydrate was calculated by subtracting the observed moisture, ash, proteins, and fat from 100% (Singh et al., 2022). The CIE LAB trichromatic coordinates ( L *, a *, and b *) were determined by a manual colorimeter (Chroma Meter CR‐400, Konica Minolta).…”
Section: Methodsmentioning
confidence: 99%